2015
DOI: 10.1073/pnas.1517638112
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of nucleotide-dependent structural transitions in the kinesin-1 hydrolysis cycle

Abstract: To dissect the kinetics of structural transitions underlying the stepping cycle of kinesin-1 at physiological ATP, we used interferometric scattering microscopy to track the position of gold nanoparticles attached to individual motor domains in processively stepping dimers. Labeled heads resided stably at positions 16.4 nm apart, corresponding to a microtubule-bound state, and at a previously unseen intermediate position, corresponding to a tethered state. The chemical transitions underlying these structural t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
222
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 119 publications
(242 citation statements)
references
References 61 publications
17
222
1
Order By: Relevance
“…Prepare a solution of 1.6 mg/mL free tubulin, 4 m M MgCl 2 , 1m M GTP, and 1:25 DMSO in BRB80 buffer, and incubate at 37°C for 30 min.Stabilize by adding taxol to 10 µ M .Dilute to working concentration (~1:80) in BRB80 plus 10 µ M taxol and 0.5 mg/mL casein. Recent work has shown that a rigor form of kinesin-1 (full-length Drosophila KHCR210A) is highly effective in microtubule immobilization (Mickolajczyk et al, 2015). The tail domain of full-length kinesin binds strongly to casein-treated surfaces, while the head domains bind tightly to microtubules.…”
Section: Methods and Protocolsmentioning
confidence: 99%
See 4 more Smart Citations
“…Prepare a solution of 1.6 mg/mL free tubulin, 4 m M MgCl 2 , 1m M GTP, and 1:25 DMSO in BRB80 buffer, and incubate at 37°C for 30 min.Stabilize by adding taxol to 10 µ M .Dilute to working concentration (~1:80) in BRB80 plus 10 µ M taxol and 0.5 mg/mL casein. Recent work has shown that a rigor form of kinesin-1 (full-length Drosophila KHCR210A) is highly effective in microtubule immobilization (Mickolajczyk et al, 2015). The tail domain of full-length kinesin binds strongly to casein-treated surfaces, while the head domains bind tightly to microtubules.…”
Section: Methods and Protocolsmentioning
confidence: 99%
“…Attachment of nanoparticle labels to kinesin, myosin, and dynein motors has to date been achieved via biotin–streptavidin chemistry (Andrecka et al, 2015; Dunn & Spudich, 2007; Isojima, Iino, Niitani, Noji, & Tomishige, 2016; Mickolajczyk et al, 2015; Schneider, Glaser, Berndt, & Diez, 2013; Schneider, Korten, Walter, & Diez, 2015). One method of introducing biotin into kinesin is to create a cysteine-lite mutant, in which solvent-exposed cysteines are mutated out of the motor domain and a single cysteine is kept to take advantage of sulfhydryl chemistry for attaching a maleimide-functionalized label.…”
Section: Methods and Protocolsmentioning
confidence: 99%
See 3 more Smart Citations